Research of the quality indices of sour milk paste - Kochubei-Lytvynenko, Oksana; Bandura (Kuzmyk), Uliana; Yushchenko (Gonchar), Natalia (My University, 2019)
One ofthe most important parameters offood quality andsafety is the indicator ofwater activity. By reducing the activity of water, the binding energy in the material is increased and, as a rule, the ability of microorganisms to use moisture for metabolism is reduced, the rate of most chemical reactions responsible for the deterioration ofdairy products is reduced.In order to confirm the effectiveness ofthe developed spice compositions for sour milk pastes and to predict the storage capacity, the water activity index was investigated. Studies of moisturebinding properties were performed by the activity ofwater (Aw). Determination was performed on a water activity analyzer "HygroLab 2 " (Rotronic, Switzerland) on the basis of the Problem Research Laboratory of the National University of Food Technologies. It wasfound that the activity offermented milk paste water (based on soft dietary non-fat cottage cheese) was 0.97, while in the control (soft dietary non-fat cottage cheese) it was 0.96. The water activity index did not undergo significant changes, which is within the error range and confirms the stability of the properties ofthe high-molecular compounds (starch, proteins, cellulose solution) during storage. Одним з найважливіших параметрів якості та безпечності продуктів харчування є показник активності води. Зменшуючи активність води, енергія зв’язку в матеріалі збільшується і, як правило, знижується здатність мікроорганізмів використовувати вологу для метаболізму, знижується швидкість більшості хімічних реакцій, що відповідають за знос молочної продукції. для підтвердження ефективності розроблених композицій спецій для кисломолочних паст та прогнозування здатності до зберігання було досліджено показник активності води. Дослідження властивостей, що зв'язують вологу, проводили за активністю води (Aw). Визначення проводили на аналізаторі водної активності "HygroLab 2" (Rotronic, Швейцарія) на базі лабораторії проблем проблем Національного університету харчових технологій. Було встановлено, що пропонована активність молочної пасти (на основі м'якого дієтичного нежирного сиру) становила 0,97, тоді як у контролі (м'який дієтичний нежирний сир) вона становила 0,96. Індекс активності води не зазнав значних змін, що знаходиться в межах похибки і підтверджує стійкість властивостей високомолекулярних сполук (крохмалю, білків, розчину целюлози) під час зберігання.
Keywords: кисломолочні пасти; прянощі; sour milk paste; spices; кафедра технології молока і молочних продуктів; кафедра технології ресторанної і аюрведичної продукції